Enhanced cell killing and apoptosis of oral squamous cell carcinoma cells with ultrasound in combination with cetuximab coated albumin microbubbles. (16th March 2018) - Narihira, Kyoichi; Watanabe, Akiko; Sheng, Hong; Endo, Hitomi; Feril, Loreto B.; Irie, Yutaka; Ogawa, Koichi; Moosavi-Nejad, Seyedeh; Kondo, Seiji; Kikuta, Toshihiro; Tachibana, Katsuro
Abstract: Targeted microbubbles have the potential to be used for ultrasound (US) therapy and diagnosis of various cancers. In the present study, US was irradiated to oral squamous cell carcinoma cells (HSC-2) in the presence of cetuximab-coated albumin microbubbles (CCAM). Cell killing rate with US treatment at 0.9 W/cm 2 and 1.0 W/cm 2 in the presence of CCAM was greater compared to non-targeted albumin microbubbles ( p  < .05). On the other hand, selective cell killing was not observed in human myelomonocytic lymphoma cell line (U937) that had no affinity to cetuximab. Furthermore, US irradiation in the presence of CCAM showed a fivefold increase of cell apoptotic rate for HSC-2 cells (21.0 ± 3.8%) as compared to U937 cells (4.0 ± 0.8%). Time-signal intensity curve in a tissue phantom demonstrated clear visualisation of CCAM with conventional US imaging device. Our experiment verifies the hypothesis that CCAM was selective to HSC-2 cells and may be applied as a novel therapeutic/diagnostic microbubble for oral squamous cell carcinoma.